Wobble Board Rehabilitation for Improving Balance in Ankles With Chronic Instability. Issue 1 (January 2016) - Linens, Shelley W.; Ross, Scott E.; Arnold, Brent L.
Abstract : Objective: To quantify improvements in clinical impairments using a wobble board rehabilitation protocol for chronic ankle instability (CAI). Design: Prospective randomized controlled trial. Setting: Laboratory. Patients: Thirty-four participants with "giving way" and history of ankle sprains were randomly assigned to a rehabilitation group (REH) (170.22 ± 8.71 cm; 75.57 ± 13.55 kg; 22.94 ± 2.77 years) or control group (CON) (168.57 ± 9.81 cm; 77.19 ± 19.93 kg; 23.18 ± 3.64 years). Interventions: Four weeks with no intervention for CON or wobble board rehabilitation for REH, consisting of 3 sessions per week of 5 repetitions. Main Outcome Measures: Dependent variables were preintervention and postintervention score on foot lift test (average number of errors), Time-in-Balance Test (TBT) (longest time), Star Excursion Balance Test (SEBT)-anteromedial, medial, and posteromedial (average reach distance normalized to leg length), side hop test (fastest time), and figure-of-eight hop test (fastest time). Results: Main effects for time were significant for all measures ( P < 0.05); but main effects for groups were not ( P > 0.05) except for SEBT-anteromedial reach direction. Significant interactions were found for all dependent measures ( P < 0.05) except for TBT ( P > 0.05). Post hoc testing of significant interactions showed REH improved performance at posttest, whereas CON did not. Conclusions: These findings demonstrate that a single intervention using a wobble board improved static and dynamic balance deficits associated with CAI. Clinical Relevance: This approach provides a potentially more economical, time efficient, and space efficient means of improving clinical outcome measures associated with CAI in patients who are physically active.